THE IMPLEMENTATION OF DICTOGLOSS TO TEACH WRITING RECOUNT TEXT TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 4 JOMBANG (RETAIN, 2014)
THE IMPLEMENTATION OF DICTOGLOSS TO TEACH WRITING RECOUNT TEXT TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 4 JOMBANG Lilis Purwaningsih English Education Department, Faculty of Language and Art, State University of Surabaya. purwaningsihlilis@gmail.com Esti Kurniasih, S.Pd., M.Pd. English Education Department, Faculty of Language and Art, State University of Surabaya. estikurniasih87@yahoo.com Abstrak Menulis adalah salah satu keterampilan penting yang harus dikuasai oleh siswa dalam mempelajari bahasa. Keterampilan ini digunakan untuk menyampaikan idea tau gagasan dalam bentuk tertulis. Lebih jauh lagi, menulis dianggap sebagai keterampilan yang paling sulit diantari keterampilan lain dalam Bahasa Inggris. Proses menulis sering membuat siswa mudah bosan. Dalam hal ini guru diharapkan mampu meningkatkan motivasi siswa agar tetap tertarik untuk menulis. Dictogloss adalah teknik mendikte yang dapat digunakan untuk mengajar menulis secara berkelompok. Teknik ini memiliki empat tahapan, yaitu persiapan, mendikte, membuat, dan analisis dan koreksi. Penelitian ini bertujuan untuk mendeskripsikan implementasi dari Dictogloss dalam menulis recount oleh kelas delapan, respon siswa, dan hasil menulis siswa. Penelitian ini merupakan jenis penelitian deskriptif kualitatif dan menggunakan observasi, kuesioner, dan tugas menulis siswa untuk mendapatkan data. Data penelitian merupakan hasil deskripsi yang dijelaskan berdasarkan tujuan penelitian. Setelah melakukan observasi, peneliti mendeskripsikan tiga hasil penelitian. Hasil pnelitian pertama menunjukkan bahwa implementasi Dictogloss yang diaplikasikan guru di dalam kelas berjalan sesuai teori Dictogloss. Hasil kedua menunjukkan bahwa siswa memberikan respon positif terhadap tenik Dictogloss, dan hasil ketiga adalah tentang hasil tulisan siswa. Tulisan siswa dianalisis dalam hal apakah isinya sesuai dengan judul, baik tidaknya penyusunan tulisan, penggunaan bahasa yang sesuai dengan recount, kosa kata sesuai, dan cara menyajikan tulisan oleh penulis. Kesimpulannya, Dictogloss dapat digunakan untuk teknik mengajar menulis recount, khususnya bagi kelas delapan yang disebut sebagai pemula Kata Kunci: Dictogloss, menulis, recount, respon siswa. Abstract Writing is one of the important language skills that should be mastered by the students to convey their ideas or their opinion in written form. Moreover, writing is known as the most difficult skill in English. Writing process often makes students easily get bored. Here, the teacher is needed to maintain students’ motivation in order to keep students’ interest in writing. Dictogloss is a technique of dictation method that can be used for teaching writing cooperatively. It has four steps; those are preparation, dictation, reconstruction, and analysis and correction. This research is aimed to describe the implementation of Dictogloss in teaching writing recount text to the eighth grade students, the students’ responses towards Dictogloss, and the students’ writing task results. This research is a descriptive qualitative research. It used observation checklist, field note, questionnaire, and also student’s task result as research instruments to gain data. The researcher endeavored to record the implementation of Dictogloss and describe it. The description is explained based on three objectives of the study; those are the implementation of dictogloss to teach writing recount text , the students’ responses towards Dictogloss, and also the students’ writing task results. After observing, the researcher described three results. The first result was regarding the implementation of dictogloss the teacher applied. The steps how the teacher applied were as appropriate as how it is in the theory and it was done well. The second result was the students’ responses toward dictogloss and it resulted positive responses. And the third finding was the students’ writing task result that was analyzed by using ESL composition profile. It has five criteria; content which is appropriate with the topic, organization which is arranged well based on the generic structure, language use which is related to the language features, vocabulary which is appropriate to what have been listed by the teacher, and mechanics related to how well the writers write their writing. In conclusion, dictogloss could be used to teach writing recount text, particularly for eight graders as beginner English learner. It could be even used to keep students’ willingness in writing because of its steps. Keywords: Dictogloss, writing, recount text, students’ response. INTRODUCTION Writing is one of the important language skills that should be mastered by the students to convey their ideas or their opinion in written form. However, writing is not a simple matter to learn since students need to have capability to convey their opinion in written form which is considered to be more difficult than spoken form. It is because there are some processes that have to be passed. As it is known that writing is very important skill, writing is needed to be taught. In writing, a teacher should encourage students to produce a text as a medium to communicate their ideas or opinions to others through written form. However, there are some problems that are found by the teacher. The first problem is the students try to avoid writing because it needs a long process to create a good writing and it is too complicated. It is supported by Pirangelo and Giuliani (2006:245) who state that students in educational system feel that writing process takes a long time, sothey are common to dislike or avoid writing activity. Moreover, writing process will make students easily get bored. Here, the teacher is needed to maintain students’ motivation in order to keep students’ interest in writing. The teacher’s role in writing class is to motivate the students, to create the right condition for generating ideas, and to encourage them to practice more to get the benefit (Harmer, 2004). The other problem is students get difficulties in organizing their ideas. In this case the teacher is needed to teach students how to manage their ideas and write them in order, so the students will produce a good writing. According to Knapp and Watkins (2005), it is important for the teacher and the students to have basic understanding of how English operates and functions as writing and the ways in which writing is different from speech. Besides two problems above, lack of vocabularies is also a problem for students to write, particularly for beginner writer. It is often that students cannot create a good writing because they do not know appropriate vocabulary for their writing. Since vocabularies make the students frustrated, the teacher should help the students by giving vocabulary preparation as their guided writing. Guided writing is an instructional writing context that mainly guides students in writing process through modeling, support, and practice (Tyner, 2004). Guided writing can be applied through a technique, such as dictogloss. Dictogloss is a technique of dictation method that can be used for teaching writing cooperatively. Dictogloss is a classroom dictation activity where learners listen to a passage, note down key words and then work (Vasiljevic, 2010). This technique is more than just dictation since students focus on meaning rather than words and it also includes interaction among students. Dictogloss can be useful for integrated skills; those are listening, speaking, reading and writing. Dictogloss is initially designed to teach grammar and it has four stages, those are preparation, dictation, reconstruction, and analysis and correction (Wajnryb, 1990). However, there are only few teachers who implement dictogloss in classroom activity, particularly in teaching writing; one of them is an English teacher of Junior High School in Jombang. The teacher uses dictogloss in teaching writing recount text for eighth grade students. Thus, dictogloss is found useful to help teacher to teach writing recount text. From the explanation above, the researcher therefore wants to conduct a research related to the implementation of dictogloss in teaching writing recount text. The researcher formulates the research question as follows: (1) How does the teacher implement dictogloss in teaching writing recount text to the eighth grade students of SMPN 4 Jombang? (2) How are the students’ responses towards the implementation of dictogloss in teaching writing recount text? (3) How are the students’ writing tasks resultsduring the implementation of dictogloss in teaching writing recount text? Writing Writing is an activity that creates ideas or opinions in a composition by using writing convention, such as its ideas or thought that are produced in written form (Petty and Jensen, 1980). Moreover, writing nowadays becomes an important skill to face the global era. It conveys that writing is used widely in every aspect of life, particularly for interacting and communicating with people, whether formal or informal writing. It is also supported by Brown (2004) who states that writing skill is an important skill for achieving employment in this global era. Thus, learning how to write for students is crucial as input for them to face the future. According to Meyers (2005), writing is an action-a process of discovering and organizing ideas, putting them on a paper, reshaping and revising them. In other words, writing has to be coherent and cohesive where the ideas in the writing should make sense and be connected logically. That statement interprets that learning writing needs more steps. The Steps of Writing There are some statements related to writing process. First, Boas (2011) says that writing is one of the English skills whose activities are planning, drafting, and revising texts. Second, Hedge (1993) argues that the processes of writing are pre-writing, while writing, and post-writing. In line with Hedge, O’Malley & Pierce (1996:254) say that there are three stages in writing process; they are pre-writing, drafting, and post-writing. Meanwhile, there are four common stages in writing process; those are planning, drafting, editing, and producing final version (Harmer, 2012:128-129). Dictogloss According to Jacobs (2003:1), dictogloss is an activity in which short pieces of language are read out at normal speed to students. In line with that, Wajnryb (1990) also states that dictogloss is a technique in which short pieces of language are read out at normal speed to students. Dictogloss is a technique which has steps in the process. There are four steps to conduct dictogloss technique; they are preparation, dictation, reconstruction, and analysis and correction (Wajnryb, 1990). 1.Preparation At this stage, teacher prepares the material which is going to be taught. The teacher introduces the topic and lists some vocabulary for the students. Moreover, the students are divided into pairs or small groups and given brainstorming before coming to the next step. 2.Dictation At this stage, the teacher reads the text twice in normal speed and asked the students to listen. On the first dictation, the teacher reminds the students to listen only and not to write anything. While on the second dictation, the teacher asks the students to prepare notebook and write down some words which will be keywords for the next step; that is reconstruction. 3.Reconstruction At this stage, the teacher asks the students to reconstruct the text based on their keywords in pairs or groups. Those keywords are used as their guided writing to produce a text which has the same idea as the original text. Holdich and Chung (2003) indicate that guided writing offers greater opportunities for young writers to make valuable connections between text, sentence and word level decisions and help students shape and redraft texts with particular criteria in mind. In conclusion, the principle of guided writing strategy is to provide instructional materials or relevant media to help students write. 4.Analysis and correction While at this stage, the teacher asks the students to analyze and correct their text result. It is also done with the teacher’s help by comparing their version to the other group or pair result, and the last comparing with the original one to see the differences. According to Jacob (2003), there are many variations of Dictogloss in learning activities. They are explained as follows: a. Dictogloss Negotiation In dictogloss negotiation, the students have chance to discuss with the partner or group about what they have heard for each section of dictation. They will get twice dictation which means that the students have two chances to discuss. b. Student Controlled Dictation In student controlled dictation, the teacher acts as a tape recorder that can be played by the students. In other words, the students can ask the teacher to stop, go back, rewind, and skip ahead. c. Student-Student Dictation In student-student dictation, the students take turns to read the text to each other. Here, the teacher’s job is just monitoring the process. d. Scrambled Sentence Dictogloss In scrambled sentence dictogloss, the teacher jumbles the sentence of the text before, so that the students have to recreate and put it into logical order first. e. Dictogloss Summaries In dictogloss summaries, the students focus only on the key ideas of the original text. Here, as well as in other dictogloss variations, the teacher can provide visual aids (sketch, flow chart, photo, mind map) that represent some elements of the story. f. Elaboration Dictogloss In elaboration dictogloss, the students go beyond what they hear to not only recreate the text, but also improve it. g. Dictogloss Opinion In dictogloss opinion, after the students reconstructed the text, they are allowed to give comment or opinion on the writer’s ideas. Those can be placed at various points in the text or can be written at the end of the text. In this research, the researcher focuses on using Dictogloss summaries to be implemented in the classroom. Recount Text Based on Basic Competence of 2006 Curriculum (BSNP, 2006), recount text is a kind of text dealing with the experiences happened in the past and focuses on a sequence of events related to the occasion which has purpose to inform or entertain the readers. That is in line with Gerot and Wignell (1994) who explain that recount is a kind of text which has function to retell past events for the purpose of informing or entertaining. In addition, recount text is a text that tells the readers about something that happened or retells past events or activities and has purpose to give detail information about what and when of those events (Anderson and Anderson, 2003). Furthermore, According to Depdiknas (2004:33), recount text has function to tell or to retell past events for the purpose of informing or entertaining. From the explanation above, it can be made some points that recount text is about retelling a series of events, written by using past tense, and it aims to inform or entertain the readers. It is essential to know and understand the steps how to construct a recount text. Anderson and Anderson (1998:28) present the generic structure of recount text clearly as below: 1. Orientation Orientation in recount text provides all necessary background information about the event. To ensure that the orientation is detailed and thorough, use the question words (who, what, when, where, and why). 2. Series of events In series of events the writer writes the events chronologically. It begins from the first event, followed by the second event to the last event. The sum of events depends on the creativity of the writer and has to lead the readers or audiences to understand the topic well. 3. Re-orientation The final section concludes the recount by summarizing the outcomes or results, evaluating the results, evaluating the topic’s importance or offering personal comment or opinion. However, not all of recounts are closed by re-orientation. It is optional. Meanwhile, recount text also has specific language features, they are using specific participant, involving some action verbs, using simple past tense, and often using linking words. Using Dictogloss to Teach Writing Recount Text Dictogloss offers a context-rich method of assessing how much students know about writing and the topic of the text (Jacobs, 2003). The text reconstruction task provides learners with opportunities to display both their knowledge of the content of the text as well as of the organizational structure and language features of the text (Derewianka, 1990). This technique provides opportunities for the students to be more confident with their writing as there is vocabulary preparation for students as beginner learners to ease them in writing. The steps of using dictogloss during teaching and learning process are described as follow: • Pre activity: The teacher greets the students and checks the students’ attendance list to know the condition of all the students. Before starting the main activity, the teacher also does brainstorming to motivate students in learning English. • Whilst activity: The teacher introduces the technique to the students. This introduction covers introducing what the technique is, what the steps are, and also what the students should do in every step. Here are the brief explanations of dictogloss: 1. Preparation Here the students are introduced with the text, the title, and also some difficult vocabulary related to the text. 2. Dictation There are two dictations which are done by the teacher. On the first dictation, the teacher asks the students to listen only. While on the second dictation, the students are asked to jot down some keywords for their reconstruction of the text. When the students come to dictation step, the teacher’s roles as reminder and also controller are very important. It is caused by on the first dictation; the students tend to write something that they hear. While on the second dictation, they tend to cheat other students’ keywords. Therefore, the consistency of the rules is really important. 3. Reconstruction The students work in pair or group in reconstructing the same text based on what they have heard and it is helped by their keywords. It has to include generic structure of the text and also the language features. 4. Analysis and Correction The students are asked to analyze their writing by comparing it with the original text and make correction of it. They analyzed in terms of vocabulary, generic structure and language use, particularly the use of tense. • Post activity The teacherreviews all points which have been covered on that day. The teacher reviews the text and also mistakes which are commonly made by the students. Previous Studies In this study, the researcher relates the study with previous studies which are dealing with dictogloss in teaching and learning process, particularly in teaching and learning writing. Rosi (2010) applied dictogloss in teaching writing narrative text to the eleventh graders. She wanted to know whether or not dictogloss could be used to teach that text. She found that students can enjoy the activities and dictogloss could be used as one alternative way to teach writing narrative text. Moreover, Rahayu (2012) conducted a research to know the implementation of dictogloss in teaching writing descriptive text. The result finally showed that dictogloss could also help the students in practice writing descriptive text. Based on the success of those previous studies above about the use of dictogloss in writing activity, the researcher wants to conduct a further research. In this research, the researcher will use the same technique but different kind of text and subject level. In this case the researcher focuses on recount text in eight grade students of SMPN 4 Jombang. RESEARCH METHODOLOGY In doing this study, the researcher used descriptive qualitative research, since it more focuses on the process rather than outcomes of the phenomena. The subjects of the study were the English teacher and the eighth grade students of SMP Negeri 4 Jombang the setting of the study was SMP Negeri 4 Jombang which is located on Jln. Mawar No.4 Denanyar, Jombang.. The researcher collected the data through some instruments. The instruments were observation checklist to gaint the data for the first research question, closed-structured questionnaire to gain data for the second research question, and students’ writing task result analyzed with Jacob’s ESL Composition Profile for the third research question. Moreover, the data were analyzed by using three stages, those are familiarizing and organizing, coding and reducing, and interpreting and representing. In the familiarizing and organizing, the data which have been gained were read and reread, checked and rechecked many times to familiarize initially and organize all of the data for easy retrieval. After that, the researcher came to the next stage, coding to categorize. The researcher sorted the data into three categories since there are three research questions in this study. The researcher also reduced some data that have no relation and could not be used to answer those three research questions. Finally, the last stage was interpreting and representing. This means that the researcher described the data and elaborated them referred to related theories and findings and represents them in the form of words, or even diagram, chart or table. RESULT AND DISCUSSION Result 1.The Implementation of Dictogloss in Teaching Writing Recount Text The implementation of dictogloss was done in two meetings; those were on Wednesday November 20th and Thursday November 21st. The time that was allocated for each meeting was 2 x 40 minutes. The First Observation There were 32 students which consist of 16 males and 16 females students. There were 16 tables and 32 chairs. They sat in pairs and in the same gender. Those tables and chairs were arranged in four columns and four lines with little space between one column to the others. The class was covered with white ceramics. On Wednesday, the class was started on the last period, it was around 11 a.m. The teacher started the class by greeting the students, checking the attendance list and asking the students’ condition. Later, the teacher continued opening session by giving the students motivation to learn English. It was given when the teacher saw the students who less motivated as it was the last period lesson. After that, the teacher explained the material that was going to learn. The teacher explained that the material was about recount text. However, the teacher also explained that this meeting would use dictogloss. The teacher introduced the main concept of dictogloss. The teacher explained the procedure of dictogloss and the students paid attention to her, but some of the students asked some questions related to her explanation. In that session, the teacher explained the procedure or the steps of dictogloss deliberately. She mentioned four steps in the dictogloss; those are preparation, dictation, reconstruction, and correction and analysis. After explaining each step, the teacher applied the technique by using the learning material entitled ‘My Child’. Preparation First of all, the teacher introduced the topic of the learning material. That was “My Child”. The teacher then asked some questions related to the title with the students’ life as brainstorming for them. Moreover, the teacher also wanted to gain prior knowledge and general information from the students. Dictation On the first time, the teacher started to dictate the text. Here the teacher again and again controlled and reminded the students not to do anything, except listening. However, in the middle of dictation, there was student who tried to write something in his notebook, and then the teacher stopped her dictation and reminded that student. After that, the teacher restarted the text from the beginning. The teacher read loudly on the normal speed. After finishing the first dictation, the teacher reminded again the rule for the second dictation that was going to do. On the second dictation, the students were allowed to write something as keywords individually. Reconstruction After the second dictation, the teacher divided the class into some pairs. Since a table consists of 2 students, the teacher tried to save the time and formed students into some pairs based on their seat. Furthermore, the teacher asked the students in pairs to reconstruct the text they had just heard by using their keywords in their notebook in 15 minutes. After that the teacher monitored the students’ group discussion. She walked around the class and sometimes asked the students to do the task together and use their keywords as reference to create the construction. The time was up and the teacher asked the students to submit it on a piece of paper. Analysis and Correction The teacher switched the students’ task result, so they did not get their own task result. Then the teacher asked them to analyze the task result which had been gotten in terms of generic structure and language features. The teacher invited at least two pairs to analyze their friends’ writing. The students in the classroom became active to defend their opinions. At the last, the teacher gave feedback and correction to the students work by showing the original text which can be used by the students to compare with their task result. Finally, the students rewrote their writing by using the correction and they submitted it again. The Second Observation The second meeting was held on 21st November 2013 in the first period. The teacher greeted the students and asked about the students’ condition. Then she checked the attendance list and called the students one by one. At that time, there was one student who was absent, so the class began with 31 students. After opening section, the teacher tried to review and remind the students about the material that had been learned the day before. After reviewing, the teacher started the lesson on that day. She said that she would apply dictogloss again, but with different text. She did not need to explain again what dictogloss is in detail. She just recalled it in general. Preparation The teacher began to introduce a new material entitled “Camping”. The teacher tried to relate the title with the students’ activity in a real life. After that, the teacher introduced some vocabulary existed in the text by writing them on the whiteboard. The teacher asked the students to guess the meaning of the words by giving them an exposure of the context. Dictation Before coming to dictation step, the teacher reminded the students about the applied rules by asking them to make sure that they still remembered and understood the rules. The teacher then read the text loudly and briefly on normal speed again. The students seemed more understand about the text. On the second dictation, the teacher reminded the students not to forget to write keywords individually during the second dictation. Most students did listing keywords individually, while some students still cheated their pair. Reconstruction After dictation, the teacher discussed the story of the text with the students. After that, the teacher asked the students to work in pair and reconstruct the text. The teacher gave the students a piece of paper and asked them to write keywords and also the task result on that piece of paper. The teacher walked around the class to monitor the students’ activity during reconstruction step. Analysis and Correction The teacher asked the students to stick the task result on the white board. Then she invited every pair to analyze one task. Every task has a space as a place for comment. The class became so noisy. After that, the teacher gave feedback and correction for the students in general. And then, the teacher showed the original text and asked the students to compare it with their writing. 2. Students’ Responses after the Implementation of Dictogloss in Teaching Writing Recount Text Students’ responses are students’ opinions or feelings after the implementation of dictogloss in learning writing recount text. In order to know their responses, questionnaire was spread out to the students to gain the data. Students’ Opinion towards Writing Writing is one of the English skills that must be learned by the eighth grade students. However, this skill is considered to be difficult for the students. It is proved by the questionnaire result that 26 of 32 students agree with that statement and 1 student strongly agree with that. While only 5 students admit that writing is not difficult. The Most Difficult Aspect Faced in Writing In addition to the result above, here are some students’ reasons why writing is considered to be difficult. There are 14 students admit that vocabulary is the most difficult aspect to be mastered in writing, as difficult as ways of arranging sentences. Moreover, there are 3 students respond that long and boring processes become the first reason of feeling difficult to write. While only one student states that it is difficult to get idea when doing writing activity. Students’ Opinion towards Vocabulary Preparation as Pre Activity In line with the previous responses which show that vocabulary is one of the most difficult problems in writing, the questionnaire result shows that giving vocabulary before starting writing is so helpful. When there is a question about whether it is needed to get vocabulary first before writing, 31 students agree with that. However, only one student who states that vocabulary is not needed to give before writing. Students’ Opinion toward Group Work Since eighth grade students are considered to be beginner learners, they often feeling hard to write when writing is done by individual. They consider collaborating with others because they could cooperate. When they were asked to work in pair, all of students agree with that. Students’ Responses towards Teacher’s Explanation of Dictogloss Dictogloss is a technique that is used in this writing activity. Before starting the activity, the teacher should introduce the technique briefly and clearly. There are 28 students comprehend the teacher’s explanation about dictoglossand its steps. While only 4 students admit that the explanation is not clear enough, so they do not completely understand of what Dictogloss is. Students’ Satisfaction When the students are asked whether or not they are satisfied with their writing result after the implementation of dictogloss, 20 students are satisfied with their writing. Meanwhile, 12 students state that they are not satisfied with their writing task result after the implementation of dictogloss. Students’ Response toward the Ease of Dictogloss In line with the previous question, whether the technique is helpful for the students in terms of vocabulary as guided writing,there are 18 students state that dictogloss is helpful for them in writing.While among 32 students, 16 students disagree and consider that the technique is just technique and cannot more help them in writing, even though it provided vocabulary preparation. Moreover, there is 1 student who states that dictogloss cannot help him in writing. Students’ Opinion toward Dictogloss Helps Students in Understanding the Material After the implementation of Dictogloss, the students were asked about the material. There are 19 students state that the technique is useful for them in understanding the material well. While 13 students have different opinion who state that dictogloss cannot help them in understanding the material. Dictogloss Motivates Students in Writing Dictogloss could be a motivational technique used for motivating students in writing recount text. Almost all students agree with that statement; there are 25 students who are motivated to finish their writing recount task after the implementation of Dictogloss. Furthermore, only 7 students disagree with that statement. Dictogloss Makes Students Confident in Writing Dictogloss helps students in writing. There are 24 students are satisfied that Dictogloss can increase their confidence in writing. Among those 24 students, 7 students strongly feel that their confidences are increasing. On the other way around, 7 of 32 students disagree with that because dictogloss does not influence their confidence. Dictogloss is a Enjoyable Technique During the implementation of dictogloss, the students enjoy to follow all technique steps and instructions. There are 21 students admit that this technique is an enjoyable technique. While 11 students state that dictogloss is just common technique. The Students’ Opinion Towards the Ease of Dictogloss Steps Dictogloss is a technique which has some steps to follow in conducting teaching and learning process. It has four steps; preparation, dictation, reconstruction, and correction and analysis. Based on the students’ point of views, 22 students could follow the steps easily; while 10 of 32 students could not. They thought that the dictogloss’ steps are difficult to follow. The Learning Materials are Appropriate for the Students In order to succeed the implementation of the technique, it is also important to get appropriate materials which are about recount text. Appropriate means the learning materials fulfilled their level as the eighth graders who learned about recount text. According to 18 students, the learning materials which they got are appropriate with their capability. While 12 students state that the learning materials are not appropriate for them. The Text is Understandable In dictation step, the teacher read a recount text twice. That was time for the students to listen and jot down some keywords. There are 15 students who respond that the recount text is understandable, while there are also 15 students who are difficult to understand the text. The Topics Lead Students’ Motivation The topic of the text should be interactive and it should attract the students. When the students listened to the dictated text, 14 students admit that the topic could lead their motivation; even there are 8 students who have high motivation. Meanwhile, 8 of 32 students are not motivated by the topic of the text. 3. Students’ Writing Task Result In order to answer the research question number three that is about students’ task result during the implementation of Dictogloss, the researcher shows the task result in this part based on some criteria. The Content of Students’ Writing Task Result Content is one of the important components in writing. Since the text is one for all, the content is related with topic, logical development of ideas, and content of each paragraph for a text. Since there are two task results, the researcher will describe both task results for each criterion. The Organization of Students Writing Task Result The second component in writing is organization. This component deals with how the writer arranges the writing based on the given title, conveys the idea clearly, and organizes the idea in each paragraph based on the generic structure of recount text. The Language Use of Students Writing Task Result The third component in writing is language use. In the description below, the researcher will describe language use used by the students, such as the use of tense, pronouns, article, modals, and also the verb. The Vocabulary of Students Writing Task Result Vocabulary is the fourth important component in writing. It deals with whether or not the writers chose good vocabulary for their writing. In this case, vocabularies which are related to the text have been listed by the teacher in the preparation step of dictogloss. Therefore, the more those vocabulary used, the better writing task result in terms of vocabulary component. The Mechanics of Students Writing Task Result The last component in writing proposed by Jacob et.al (1981)is mechanics. In this study, mechanics are dealing with spelling, punctuation, capitalization, and paragraphing. Discussion There are three results to be discussed in this part. Firstly, related to the observation checklist result as the first result regarding the overview of the implementation of dictogloss, whether it is applicable to be applied to teach writing or not. Secondly, related to the second result of the close-structured questionnaire which could give brief explanation about the students’ responses towards dictogloss, whether positive or negative. Thirdly, the students’ writing task result as the result used to know whether or not dictogloss is workable to help the students in writing recount text. Dictogloss was applied in two meetings. It was done in four steps; those are preparation, dictation, reconstruction, and analysis and correction. Those steps were appropriate to dictogloss as proposed by Wajnryb (1990). The implementation of dictogloss had gained the students’ responses. The students’ responses are various opinions showed in the close-structured questionnaire. The researcher provided 15 questions in the questionnaire based on three main categories; those are writing activity, the implementation of dictogloss, and the learning material. Firstly, the students showed their opinion toward writing activity. Most students said that writing is difficult and it is the most frustrating activity for the students. It is in line with Nunan (1999) who stated that writing is known as the most difficult skill in English. Secondly, the students responded the implementation of dictogloss as the teaching writing technique. The students gave opinion regarding the four steps of dictogloss; those are preparation, dictation, reconstruction, and analysis and correction. Most of the students said that the steps are easy to follow because the teacher gave them clear instruction. Furthermore, the students said that dictogloss gives positive side toward their writing. Thirdly, the students gave opinion regarding the learning material. In terms of the text, most of the students stated that the texts in two meetings contain attractive, motivating, and also understandable topic of the text. Even, based on the result of questionnaire, most of them agreed that the text could make them confident on their writing. In general, the students responded positively toward the use of dictogloss in writing in terms of the writing activity, implementation, and also the learning material. The students were asked to reconstruct a text every meeting. During the research, there were two writing task results and the researcher analyzed them using ESL composition profile proposed by Jacob et al (1981). This writing composition consists of five writing components; those are content, organization, language use, vocabulary, and mechanics. The first component is content, the researcher analyzed the relationship between the topic and the students’ writing task result. Based on the two submitted writing task results, most of the students were able to relate their writing with the topic. The second component is organization, the researcher would analyze whether the students’ writing task results were well organized and appropriate to the generic structure of recount text. The third component is language use, the teacher analyzed whether the use of tense, pronouns, article, modals, and also the verb are correct. The fourth component is vocabulary. Since there is preparation step where related vocabularies are listed, the students were expected to use those vocabularies when they reconstructed their writing. The last component is mechanics. Here, the researcher analyzed how the writers presented their writing; in terms of spelling, punctuation, capitalization, and paragraphing. CONCLUSSION AND SUGGESTIONS Conclussion In conclusion, the implementation of dictogloss to teach writing recount text did run well. In addition, the students’ responses are positive toward dictogloss, which help most of them in reconstructing the text in terms of providing them vocabulary for their writing. Furthermore, dictogloss is also workable to help most of students in writing recount text. Moreover, the result of the students’ writing tasks was satisfying. It means that Dictogloss could help most of the students in writing, particularly in terms of vocabulary as their guidance before writing. Suggestions At the end of this study, the researcher would like to give some suggestions which are hoped to be useful to enhance the quality of teaching and learning process, particularly in writing. The teacher should be more creative in creating attractive and interesting class for teaching writing recount text. Besides, the teacher also has to pay attention to the students’ need. The teacher should have many ideas to be implemented. Dictogloss is one of the techniques that cannot only help the students in writing, but also motivate them in learning other skills. While for the next researcher, there must be further research in the same study; it is expected for the next researcher to do research in different areas of dictogloss, the implementation of dictogloss in different skills, grade and for different kinds of text, for instance. REFERENCES Anderson, M., & Anderson, K. 1998.Text Types in English. South Melbourne: MacMillan EducationAustralia. Anderson, M. & Anderson, K. 2003.Text Types in English 1. South Yarra, Victoria: MacMillan Education Australia. Ary, D., Jacobs, L. C., Sorensen, C., & Razavieh, A. (2010). Introduction to Research in Education. Wadsworth: Cengage Learning. BadanStandarNasionalPendidikan. 2006. Standar Isi danStandarKompetensiLulusan: Mata PelajaranBahasaInggris. Jakarta: National education department. Boas, V. (2011) Process Writing and the Internet: Blogs and Ning Networksin the Classroom. Retrieved September 29, 2008, from http://English TeachingForum Journal, Vol. 49 (2) pp. 26-33. Brown, H. Douglas. 2004. Language Assessment: Principles and Classroom Practices. New York: Pearson Education. Cohen, L., Manion, L., & Morinson, K. (Eds.). (2007). Research Methods in Education (Vol. 7). London: Routledge Falmer. Depdiknas.2004. StandarKompetensi Mata PelajaranBahasaInggrisuntuk SMA dan MA. Jakarta: Depdiknas. Derewianka, B. 1990.Exploring How Texts Work. Newtown: PETA. Diaz-Rico, Lyne T. 2004. Teaching English Learners: Strategies and Methods.California State University, San Bernardino: Pearson Education, Inc. Gerot, L, and Wignell P. 1994.Making Sense of Functional Grammar. Sydney:GerdStabler Antipodean Educational Enterprises. Harmer, Jeremy. 2002. The Practice of English Language Teaching (Third Edition). Harlow, England: Longman. Harmer, Jeremy. 2004. How To Teach Writing. New York: Longman. Harmer, Jeremy. 2007. The Practice of English Language Teaching: Fourth Edition. London: Longman. Harmer, Jeremy. 2012. ESSENTIAL. Teacher Knowledge: Core in English Language Teaching. Edinburg Gate: Pearson Education United. Hedge, T. 1993. Writing. Oxford: Oxford University Press. Holdich, C. E., & Chung, P. W. H. (2003). A ‘computer tutor’ to assist children develop their narrative writing skills: conferencing with HARRY. International Journal of Human-Computer Studies, 59(5), 631–669. Jacobs, George. 2003. Combining Dictogloss and Cooperative Learning to Promote Language Learning. The Reading Matrix.Vol. iii No.1. Jacobs, Holly L, et al. 1981. Testing ESL Composition: A Practical Approach.Rowley: Massachusetts New Burry House Publisher Inc. Knapp, Peter and Watkins, Megan. 2005. Genre, Text, Grammar: Technologies for Teaching and Assessing Writing. Sydney NSW 2052 AUSTRALIA: University of New South Wales Press. Mather, Nancy, Wendling J. Barbara, and Robets, Ria. 2009. Writing Assessment and Instruction for Students with Learning Disabilities. New York: Jossey- Bass. Meyers, Allan. 2005. Gatewaysto Academic Writing: Effective Sentences, Paragraph, and Essays. New York: Longman. Nunan, David. 1999. Second Language Teaching and Learning. Boston: Heinle and Heinle Publishers. O’Malley, J.M., & Pierce, L.V. 1996. Authentic Assessment for English Language Learners: Practical Approached for Teachers. Redding, MA: Addison-Wesley. Pierangelo, R. & Giuliani, G. (2006).Assessment in special education: A practical approach (2nd edition). Boston: Allyn and Bacon. Petty, W. T., & Jensen, J. M. (1980).Developing Children's Language. Boston: Allyn& Bacon. Rahayu, WiekeDwi. 2009. Dictogloss in Teaching Writing Descriptive Text to the Tenth Graders.Un-published S-1.State University of Surabaya. Rosi, Sandrina. 2010. Using Dictogloss as an Alternative Technique in Teaching Writing Narrative Text to the Eleventh Graders. Un-published S-1.State University of Surabaya. Susanti, Aprilia. 2010. The Effectiveness of Using “Mapping Spot the Dictogloss” Technique in Teaching Listening to the Eighth Grade Students of Junior High School. Un-published S-1.State University of Surabaya. Tyner, B. (2004). Beginning reading instruction and the small-group differentiated reading model. In Small-Group Reading Instruction (pp. 1–16). Newark, DE: International Reading Association. Wajnryb, R. 1990. Grammar Dictation. Oxford: Oxford University Press. Vasiljevic, Zorana. (2010). Dictogloss as an Interactive Method of Teaching Listening Comprehension to L2 Learners.English Language Teaching, 3 (1), 41-52.